Repolarization Alternans Reveals Vulnerability to Human Atrial Fibrillation - Narayan, Sanjiv M. (2011)
BACKGROUND: The substrates for human atrial fibrillation (AF) are poorly understood but involve abnormal repolarization (action potential duration, APD). We hypothesized that beat-to-beat oscillations in APD may explain AF substrates and why vulnerability to AF forms a spectrum from control subjects without AF to patients with paroxysmal then persistent AF. METHODS AND RESULTS: In 33 subjects (12 persistent AF, 13 paroxysmal AF, 8 controls without AF), we recorded left (n=33) and right (n=6) atrial APD on pacing from cycle lengths (CL) 600–500 ms (100–120 beats/min) to AF. APD alternans required progressively faster rates for patients with persistent AF, paroxysmal AF and controls (CL 411±94 vs 372±72 vs 218±33 ms; p<0.01). In AF patients, APD alternans occurred at rates as slow as 100–120 beats/min, unrelated to APD restitution (p=NS). In this milieu, spontaneous ectopy initiated AF. At fast rates, APD alternans disorganized to complex oscillations en route to AF. Complex oscillations also arose at progressively faster rates for persistent AF, paroxysmal AF and controls (CL: 316±99 vs 266±19 vs 177±16 ms; p=0.02). In paroxysmal AF, APD oscillations amplified prior to AF (p<0.001). In controls, APD alternans arose only at very fast rates (CL < 250 ms; p<0.001 vs AF groups) just prior to AF. In n=4 AF patients in whom rapid pacing did not initiate AF, APD alternans arose transiently then extinguished. CONCLUSIONS: Atrial APD alternans reveals dynamic substrates for AF, arising most readily (at lower rates and higher magnitudes) in persistent AF then paroxysmal AF, and least readily in controls. APD alternans preceded all AF episodes, and was absent when AF did not initiate. The cellular mechanisms for APD alternans near resting heart rates require definition.